2011
DOI: 10.1007/s10646-011-0796-9
|View full text |Cite
|
Sign up to set email alerts
|

Single and combined effects of selected pharmaceuticals at sublethal concentrations on multiple biomarkers in Carassius auratus

Abstract: In this study, the sublethal effects of caffeine, sulfamethoxazole and their mixture on goldfish (Carassius auratus) were investigated, the biomarkers including acetylcholinesterase (AChE) in brain, 7-ethoxyresorufin O-deethylase (EROD), glutathione S-transferase (GST) and superoxide dismutase (SOD) in liver and vitellogenin (VTG) in serum were determined after 1, 2, 4, and 7 days of exposure. AChE activity was significantly inhibited by caffeine (≥0.4 mg/l), sulfamethoxazole (≥0.4 mg/l) and their mixtures (≥0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
1
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(31 citation statements)
references
References 56 publications
2
25
1
3
Order By: Relevance
“…GPx activity was inhibited in the M2 group ( Figure 2B), which may be caused by NSAIDs, which inhibit this enzyme as individual substances. Although a reduction in GPx activity might enhance the toxic effects of the tested substances on fish (Li et al 2012), no differences in LPO levels between the control and experimental groups exposed to the mixtures were found in our study.…”
Section: Discussioncontrasting
confidence: 82%
“…GPx activity was inhibited in the M2 group ( Figure 2B), which may be caused by NSAIDs, which inhibit this enzyme as individual substances. Although a reduction in GPx activity might enhance the toxic effects of the tested substances on fish (Li et al 2012), no differences in LPO levels between the control and experimental groups exposed to the mixtures were found in our study.…”
Section: Discussioncontrasting
confidence: 82%
“…The absence of change of SOD, CAT and GPx activities suggests that the processes that involved uptake, distribution, metabolism and excretion of AZT, via bile, in the liver of O. niloticus did not generate sufficient ROS to induce the responses of these enzymes. However, the exposure to the macrolides roxythromycin (20 days) and erythromycin (28 days) (Liu, Lu, Wang, Yan, Yang & Ding ) and the sulfamethoxazole, a synthetic sulphonamide antibiotic (Li, Lu, Yang & Wang ), induced SOD activity in the liver of Carassius auratus at lower concentrations than those used in this study. CAT inhibition was found in O. niloticus exposed to enrofloxacin, a fluoroquinolone antibiotic, via water and diet exposure (Andrieu, Rico, Phu, Huong, Phuong & Brink ).…”
Section: Discussionmentioning
confidence: 56%
“…Indeed, cytochrome p450 response is very early and transitory. Usually EROD activity is modified during all exposure time with organic pollutants (Curtis et al 2011;Martín-Díaz et al 2009) but some authors also showed a transitory response of EROD activity in case of exposure with different xenobiotics (PaB, PCP, pharmaceutics compounds, caffeine) in several organisms (bivalves, fishes) (Binelli et al 2006;Li et al 2012;Monari et al 2009;Thibaut and Porte 2008).…”
Section: Discussionmentioning
confidence: 99%